2022
DOI: 10.1101/2022.05.24.493260
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nitric oxide is not responsible for the initial sensory-induced neurovascular coupling response in mouse cortex

Abstract: Neurovascular coupling ensures that changes in neural activity are accompanied by localised changes in cerebral blood flow. While much is known about the involvement of excitatory neurons in neurovascular coupling, the role of inhibitory interneurons is unresolved. While nNOS-expressing interneurons have been shown to be capable of eliciting vasodilation, the role of nitric oxide in functional hyperemia remains a matter of debate. Therefore in the present study we applied a combination of optogenetic and pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 80 publications
0
0
0
Order By: Relevance
“…4. Comparison of experimental data [18] and numerical model for whisker stimulation with LNAME injected shows the model results for the optogenetic condition when LNAME is introduced.…”
Section: Lname Conditionmentioning
confidence: 92%
See 4 more Smart Citations
“…4. Comparison of experimental data [18] and numerical model for whisker stimulation with LNAME injected shows the model results for the optogenetic condition when LNAME is introduced.…”
Section: Lname Conditionmentioning
confidence: 92%
“…Experimental data are taken from experiments performed by Lee et al [18], in which full experimental details can be found. In brief, stimulation-evoked cortical haemodynamic responses were measured using 2-Dimensional Optical Imaging Spectroscopy (2D-OIS: [19]), which allows the measurement of relative changes in oxyhaemoglobin (HbO), deoxyhaemoglobin (HbR) and total haemoglobin (HbT).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations